SKIN STRUCTURE AND PATIENT CARE WITH SKIN BURNS (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article provides detailed information on the structure and functions of human skin, as well as the basic principles of patient care in case of burn injuries. It is also useful for medical workers, nurses and relatives of patients, and contains practical instructions on proper care for burn injuries.